(untitled) (Journal of the College of Basic Education, 2022)
In the present study, measurements of alpha/beta contamination and gamma dose rates measurements were carried out in scrap yard contaminated by spillage of sludge contained 238U at Al-Tuwaitha Nuclear Site. Alpha/beta surface soil contamination levels were directly measured in the field at January 2016 using RadEye SX monitor. Gamma dose rates measurements were conducted using RadEye PRD. The results showed that alpha/beta surface soil contamination levels varied from 0.1 for uncontaminated areas and reach 2.8 Bq/cm2 for contaminated areas, with an average value of 0.8 Bq/cm2, which is more than 6 times the local natural background level. Results of dose assessment indicate that, the potential radiation doses to on-site workers from site contaminants were estimated to be in the order of 0.036 mSv/y, which was considered within the occupational dose limit of 20 mSv/y recommended in the International Atomic Energy Agency (IAEA) GSR Part 3 (2014). However, the mean dose rate reaches 4.5 times the background level, indicating that remediation of site contaminants is recommended to ensure environmental safety.